SARS-CoV-2-induced multisystem inflammatory syndrome in a young adult: Case report - Bulut, H.; Herbers, A. H. E.; Hageman, I. M. G.; Netten, P. M.; de Jonge, H. J. M.; Joustra, R.; van de Veerdonk, F. L.; de Jager , C. P. C. (SN Comprehensive Clinical Medicine, 2021)
We describe a case of a previous healthy 20-year-old male athlete who presented with an atypical clinical profile with multiorgan involvement within five weeks after confirmed SARS-CoV-2 infection, suggestive for multisystem inflammatory syndrome (MIS); MIS is a rare, potentially life-threatening complication associated with SARS-CoV-2. MIS shares similar clinical features compatible with several overlapping lifethreatening hyperinflammatory syndromes, such as incomplete Kawasaki Disease (KD) and toxic shock syndrome (TSS) associated to a cytokine storm suggestive of a macrophage activation syndrome (MAS) without fulfilling the criteria for hemophagocytic lymphohistiocytosis (HLH), that may create a great challenge to distinguish between them. MIS should promptly be considered and treated, as uncontrolled MIS has a high mortality.